139k views
1 vote
Harry is trying to solve the equation y = 2x2 − x − 6 using the quadratic formula. He has made an error in one of the steps below. Find the step where Harry went wrong. Step 1: x equals the negative of negative 1 plus or minus the square root of the quantity negative one squared minus 4 times 2 times negative six, end quantity, all over 2 times 2. Step 2: x equals the negative of negative 1 plus or minus the square root of negative one plus forty-eight all over two times 2. Step 3: x equals the negative of negative 1 plus or minus the square root of forty-seven all over two times 2. Step 4: x equals 1 plus or minus the square root of forty-seven all over 4.

User Maciej M
by
6.0k points

2 Answers

3 votes
I believe it would be step number 2... I am not very sure...
User Dallonsi
by
5.3k points
2 votes

Answer:

Error is in step 2

Explanation:

Harry is trying to solve the equation y = 2x^2 − x − 6 using the quadratic formula. He has made an error in one of the steps below.

Step 1:
x= (-(-1)+-√((-1)^2-4(2)(-6)) )/(2(2))

Step 2:
x= (-(-1)+-√(-1+48))/(2(2))

Step 3:
x= (-(-1)+-√(47))/(2(2))

Step 4:
x= (1+-√(47))/(4)

Quadratic formula is


x= (-(b)+-√((b)^2-4(a)(c)) )/(2(a))

From the given equation a= 2, b= -1 and c= -6

plug in all the values in the formula

Step 1:
x= (-(-1)+-√((-1)^2-4(2)(-6)) )/(2(2))

Step 1 is correct

(-1)^2 = -1 times -1 = +1 (negative times negative is positive)

Instead of +1 , Harry used -1 inside the square root

So the error is in step 2

Step 2:
x= (-(-1)+-√(1+48))/(2(2))

User TeaBaerd
by
5.5k points